1.1. Given: (i) \( A=60^{\circ} \) and \( B=30^{\circ} \) (ii) \( A=110^{\circ} \) and \( B=50^{\circ} \) (iii) \( A=225^{\circ} \) and \( B=135^{\circ} \) Use a calculator to evaluate each of the following: (a) \( \cos (A-B) \) (b) \( \cos A-\cos B \) (c) \( \cos A \cos B+\sin A \sin B \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Mind Expander
Let's go through the given pairs of angles one by one and calculate the required values. ### For \( A = 60^{\circ} \) and \( B = 30^{\circ} \): 1. **(a)** \( \cos (A-B) = \cos(60^{\circ} - 30^{\circ}) = \cos(30^{\circ}) = \frac{\sqrt{3}}{2} \) 2. **(b)** \( \cos A - \cos B = \cos(60^{\circ}) - \cos(30^{\circ}) = \frac{1}{2} - \frac{\sqrt{3}}{2} = \frac{1 - \sqrt{3}}{2} \) 3. **(c)** \( \cos A \cos B + \sin A \sin B = \cos(60^{\circ}) \cos(30^{\circ}) + \sin(60^{\circ}) \sin(30^{\circ}) = \left(\frac{1}{2} \cdot \frac{\sqrt{3}}{2}\right) + \left(\frac{\sqrt{3}}{2} \cdot \frac{1}{2}\right) = \frac{\sqrt{3}}{4} + \frac{\sqrt{3}}{4} = \frac{\sqrt{3}}{2} \) ### For \( A = 110^{\circ} \) and \( B = 50^{\circ} \): 1. **(a)** \( \cos (A-B) = \cos(110^{\circ} - 50^{\circ}) = \cos(60^{\circ}) = \frac{1}{2} \) 2. **(b)** \( \cos A - \cos B = \cos(110^{\circ}) - \cos(50^{\circ}) \approx -0.342 - 0.643 = -0.985 \) 3. **(c)** \( \cos A \cos B + \sin A \sin B = \cos(110^{\circ}) \cos(50^{\circ}) + \sin(110^{\circ}) \sin(50^{\circ}) \approx -0.342 \cdot 0.643 + 0.939 \cdot 0.766 \approx -0.220 + 0.719 = 0.499 \) ### For \( A = 225^{\circ} \) and \( B = 135^{\circ} \): 1. **(a)** \( \cos (A-B) = \cos(225^{\circ} - 135^{\circ}) = \cos(90^{\circ}) = 0 \) 2. **(b)** \( \cos A - \cos B = \cos(225^{\circ}) - \cos(135^{\circ}) = -\frac{\sqrt{2}}{2} - (-\frac{\sqrt{2}}{2}) = 0 \) 3. **(c)** \( \cos A \cos B + \sin A \sin B = \cos(225^{\circ}) \cos(135^{\circ}) + \sin(225^{\circ}) \sin(135^{\circ}) = \left(-\frac{\sqrt{2}}{2} \cdot -\frac{\sqrt{2}}{2}\right) + \left(-\frac{\sqrt{2}}{2} \cdot \frac{\sqrt{2}}{2}\right) = \frac{1}{2} - \frac{1}{2} = 0 \) Thus, the calculations yield the following results: 1. For \( (A=60^{\circ}, B=30^{\circ}) \): - \( (a) \ \frac{\sqrt{3}}{2}, \ (b) \ \frac{1 - \sqrt{3}}{2}, \ (c) \ \frac{\sqrt{3}}{2} \) 2. For \( (A=110^{\circ}, B=50^{\circ}) \): - \( (a) \ \frac{1}{2}, \ (b) \ -0.985, \ (c) \ 0.499 \) 3. For \( (A=225^{\circ}, B=135^{\circ}) \): - \( (a) \ 0, \ (b) \ 0, \ (c) \ 0 \)